A wavelet based watermarking algorithm for video - Hussin, Saleh; Babakr, Elsadig; Ramli, Abd Rahman; Al-Hadad, Sayed R. (2005)
Nowadays, digital contents can be copied easily because of the development of digital technology. So digital watermarking technique which aims at copyright protection of digital contents becomes more and more important, and various watermarking methods have been proposed. In this paper, a video watermarking algorithm based on wavelets is proposed. In this algorithm, to achieve better imperceptibility and robustness a binary image watermark is inserted into the middle frequency subband coefficients of the blue component of the video frame. In order to improve the strength of the components of the watermark, we propose to use simple permutation method based on Fibonacci numbers to randomize the video frame in which the watermark is inserted. The proposed algorithm has been tested and the results shown that a robust watermark can be embedded in video sequences, and extracted after different attacks, in particular noise addition and filtering.